The Cotton Boll: The Relationship of Species and Genotype with Temporal Development of Boll Wall Thickness. Issue 3 (1st May 2019) - Esquivel, Jesus F.; Hinze, Lori L.
Abstract : Cotton ( Gossypium spp. L.) is a high‐value cash crop worldwide, and numerous pest insects can injure the developing cotton boll, thereby reducing yields and fiber quality. Thickness of the boll wall may be instrumental in deterring these seasonal pests, but the temporal development, or rate at which the boll wall thickens, is not known. The objective of this study was to determine boll wall thickness in four cotton species ( G. arboreum L., G. barbadense L., G. herbaceum L., and G. hirsutum L.) and among selected entries within species at selected boll ages. Temporal boll wall thickness differed significantly between cotton species, as well as among entries within species. Overall, mean wall thickness was significantly affected by cotton species and boll age. When boll ages were pooled, G. barbadense possessed significantly higher mean wall thickness than G. arboreum, G. hirsutum, and G. herbaceum . When cotton species were pooled, maximum wall thickness was observed at 14 d after flowering, followed by 21 d after flowering, and these were significantly greater than at 3, 7, and 28 d after flowering. Within all species, temporal differences in wall thickness were observed between and among entries evaluated. These findings improve our understanding of boll wall development and provide a foundation for screening cotton germplasm to potentially select for increased wall thickness as a source of pest resistance.